The Influence of Perceived Success Likelihood on Religious Boycott Intention Through Attitude Mediation - Dhiya Shafa; Citra Kusuma Dewi; Putu Nina Madiawati (Journal of The Community Development in Asia, 2025)
Religious-based boycotts have gained global relevance as consumers respond to sociopolitical and ethical concerns. This study investigates how perceived success likelihood influences intention to participate in religious boycotts, with attitude toward the boycott acting as a mediating variable. Grounded in the Theory of Planned Behavior (TPB), the research tests four hypotheses using Structural Equation Modeling-Partial Least Squares (SEM-PLS) based on responses from 225 Indonesian participants. The results reveal that perceived success likelihood has a strong positive effect on attitude (? = 0.776, p 0.001), which in turn significantly influences intention to participate (? = 0.809, p 0.001). While perceived success likelihood also shows a significant direct effect on intention, this becomes non-significant when attitude is included, indicating full mediation. These findings highlight the critical role of perceived campaign effectiveness in shaping consumer attitudes and driving participation in religious boycotts. The study contributes to the literature on consumer activism and offers practical insights for advocacy organizations aiming to strengthen public engagement through strategically crafted messages